Monetary Neutrality with Sticky Prices and Free Entry - Bilbiie, Florin O. (The Review of Economics and Statistics, 2021)
Monetary policy is neutral even with fixed prices if free entry determines product variety optimally, as in Dixit and Stiglitz (1977). Entry substitutes for price flexibility in the welfare-based price index when individual prices are sticky. In response to aggregate demand expansions, the intensive (quantity produced of each good) and ex tensive (number of goods being produced) margins move in offsetting ways, leaving aggregate production unchanged. Price stickiness thus generates deviations from monetary neutrality only in conjunction with entry frictions: when variety is not optimally determined (preferences are not Dixit-Stiglitz) or when entry is subject to sunk costs and lags. Wage stickiness instead implies nonneutrality even in the frictionless-entry benchmark.